Symmetrical Dimethylarginine as a Diagnostic Parameter in Hermann's Tortoises (Testudo hermanni) - Lehmann, Verena; Altherr, Barblin; Pantchev, Nikola; Öfner, Sabine; Zablotski, Yury; Murphy, Rachel; Coyne, Michael; Kölle, Petra (Frontiers in Veterinary Science, 2022)
Background Despite improvements in habitational conditions, kidney disease is relatively common in tortoises. Objectives Purpose of this study was the establishment of Symmetrical dimethylarginine (SDMA) reference values for clinically healthy Hermann's Tortoises. Animals Clinically healthy Hermann's Tortoises (n = 131) were included in the period from October 2017 to September 2019. Methods Creatinine and other biomarkers were tested at IDEXX Laboratories, Germany using residual blood samples from Hermann's tortoises. SDMA was measured with the IDEXX test and verified by liquid chromatography-mass spectrometry at IDEXX Laboratories, USA. Results SDMA values ranged from 1 to 21 μg/dl (n = 131) for the IDEXX SDMA Test and SDMA values ranged from 1 to 17 μg/dl (n = 82) for LC-MS. For the comparison of the two measuring systems, the following results were obtained R2 = 0.75 (p < 0.001). Conclusion and Clinical Importance SDMA can be measured in Hermann's Tortoises and the reference values range in clinically healthy animals is comparable to that of dogs and cats.